Islamic Law and Environmental Sustainability: Maqasid al-Sharia's Perspective - Nurholis, Muhamad (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2025)
This study examines the relationship between Islamic law and environmental sustainability through the perspective of maqasid al-shariah. The increasing ecological crisis, including climate change, deforestation, and pollution, demonstrates the urgent need for ethical and legal frameworks that go beyond conventional approaches. The main objective of this research is to explore how the principles of maqasid al-shariah, particularly the preservation of life (hifz al-nafs) and wealth (hifz al-mal), can be applied to support environmental sustainability. The research employs a qualitative-descriptive method with a normative-theological approach, focusing on the analysis of Qur’anic verses, hadith, classical Islamic legal texts, and contemporary studies on maqasid al-shariah. The findings indicate that Islamic law provides a strong ethical foundation for ecological balance, encouraging policies such as community-based forest management, biodiversity conservation, and sustainable use of natural resources. In conclusion, maqasid al-shariah serves not only as a theological principle but also as a practical guideline that can strengthen ecological justice and sustainability. This study contributes to the discourse by highlighting the relevance of Islamic legal objectives in addressing modern environmental challenges.   [Penelitian ini mengkaji hubungan antara hukum Islam dan keberlanjutan lingkungan melalui perspektif maqasid al-syariah. Krisis ekologi yang semakin meningkat, seperti perubahan iklim, deforestasi, dan polusi, menunjukkan perlunya kerangka etis dan hukum yang melampaui pendekatan konvensional. Tujuan utama penelitian ini adalah mengeksplorasi bagaimana prinsip maqasid al-syariah, khususnya pemeliharaan jiwa (hifz al-nafs) dan harta (hifz al-mal), dapat diterapkan untuk mendukung keberlanjutan lingkungan. Metode penelitian yang digunakan adalah kualitatif-deskriptif dengan pendekatan normatif-teologis melalui analisis ayat-ayat Al-Qur’an, hadis, teks hukum Islam klasik, serta kajian kontemporer tentang maqasid al-syariah. Hasil penelitian menunjukkan bahwa hukum Islam memberikan landasan etis yang kuat bagi terciptanya keseimbangan ekologi, termasuk melalui kebijakan pengelolaan hutan berbasis masyarakat, konservasi keanekaragaman hayati, dan pemanfaatan sumber daya alam secara berkelanjutan. Kesimpulannya, maqasid al-syariah tidak hanya berfungsi sebagai prinsip teologis, tetapi juga sebagai pedoman praktis yang dapat memperkuat keadilan ekologis dan keberlanjutan. Studi ini memberikan kontribusi dengan menegaskan relevansi tujuan hukum Islam dalam menghadapi tantangan lingkungan modern.]